Obstructing colonic stricture due to intraluminal plastic foreign body - M.T. Botchway; A. Diakakis; C. Westgarth-Taylor (Elsevier, 2019)
Bezoars are not the usual cause of intestinal obstruction in children. Due to the fact that they cannot be digested, they accumulate in the digestive tract causing blockage. We review the clinical management of a two year old boy who presented with a partial bowel obstruction from a plasticobezoar.